2017
DOI: 10.3310/hta21210
|View full text |Cite
|
Sign up to set email alerts
|

Seal or Varnish? A randomised controlled trial to determine the relative cost and effectiveness of pit and fissure sealant and fluoride varnish in preventing dental decay

Abstract: Background Fissure sealant (FS) and fluoride varnish (FV) have been shown to be effective in preventing dental caries when tested against a no-treatment control. However, the relative clinical effectiveness and cost-effectiveness of these interventions is unknown. Objective To compare the clinical effectiveness and cost-effectiveness of FS and FV in preventing dental caries in first permanent molars (FPMs) in 6- and 7-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 43 publications
1
58
0
3
Order By: Relevance
“…Any of these approaches comply with the Department of Health's "Delivering Better Oral Health Toolkit" guidelines for high-risk children. 24 However, Chestnutt et al 25 have shown that twice-yearly application of fluoride varnish resulted in caries prevention that is not significantly different from that obtained by applying and maintaining fissure sealants after 36 months, with fluoride varnish being more cost-effective, although this was in a deprived population and in a community rather than dental clinic setting. 25…”
Section: Management Of Vignettementioning
confidence: 99%
“…Any of these approaches comply with the Department of Health's "Delivering Better Oral Health Toolkit" guidelines for high-risk children. 24 However, Chestnutt et al 25 have shown that twice-yearly application of fluoride varnish resulted in caries prevention that is not significantly different from that obtained by applying and maintaining fissure sealants after 36 months, with fluoride varnish being more cost-effective, although this was in a deprived population and in a community rather than dental clinic setting. 25…”
Section: Management Of Vignettementioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] Around the same time that non-dental providers were being included as key partners in increasing access to oral health, the Interprofessional Education Collaborative (IPEC), a group of leaders in health care education from nursing, medicine, dentistry, osteopathy, public health, and pharmacy, developed the Core Competencies for Interprofessional Collaborative Practice. Primary care providers have been asked to incorporate oral health into their primary care practices by performing an oral health assessment on all children starting at six months or irst tooth eruption, whichever comes irst; initiating preventive oral health interventions such as FV every three to six months (depending on risk status) and/or luoride supplementation; counseling on nutrition and oral hygiene as needed; and establishing a dental home by the age of one year.…”
mentioning
confidence: 99%
“…Primary care providers have been asked to incorporate oral health into their primary care practices by performing an oral health assessment on all children starting at six months or irst tooth eruption, whichever comes irst; initiating preventive oral health interventions such as FV every three to six months (depending on risk status) and/or luoride supplementation; counseling on nutrition and oral hygiene as needed; and establishing a dental home by the age of one year. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Around the same time that non-dental providers were being included as key partners in increasing access to oral health, the Interprofessional Education Collaborative (IPEC), a group of leaders in health care education from nursing, medicine, dentistry, osteopathy, public health, and pharmacy, developed the Core Competencies for Interprofessional Collaborative Practice. 16,17 This document delineates basic interprofessional competencies, such as respecting each other's values, understanding each other's roles and responsibilities, communicating, collaborating, and team functioning, which all students in the health professions need to develop to provide better, safer, more cost-efective whole person care.…”
mentioning
confidence: 99%
“…Similar to spatial microsimulation, there is also the potential for agent‐based models to help reduce costs associated with research. For example, recent trials in dentistry have been funded for sums of £1.3 million and £2.9 million, for studies comparing the clinical efficacy and cost‐effectiveness of fissure sealants and fluoride varnish in preventing caries, and an investigation of effective approaches to managing decay in children's teeth, respectively. Given the open source nature of many datasets, and even accounting for the cost of researchers and computing power, agent‐based modelling approaches are likely to present substantial savings.…”
Section: Where Are We Now?mentioning
confidence: 99%